Teaching and Learning Speaking For The First Grade of Nursing Academy In Academic Year of 2019/2020 - Dwi Heriyanto; Atik Muhimatun Asroriyah (English Education and Literature Journal (E-Jou), 2022)
The problems of the study are : (1) how is the teaching and learning process of speaking English of the first grade of Nursing Academy of Purworejo regency in Academic Year of 2019/2020. (2) Whyare the problems found during the teaching and learning process of speaking English of the first grade of Nursing Academy of Purworejo Regency. Tehe theories which are used as a basis of this. Study are the nature of language, teaching and learning, the model of curiculum in Nursing Academy. Teaching and learning of speaking English, the lesson plan of speaking English, media and the source of learning, act. Based on the data analysis, it can be concluded that: (1) Some Casees occur during the teaching and learning of speaking English . (2) the students find the difficulties in pairing and perfoming speaking because the situdents limited of vocabularies, pronounciation, and grammar mastery. This research is a casestudy done at the first grade of Nursing Academy Purworejo regency in Academic Year of 2019/2020. The technique of sampling is purposive sampling. The data to get from: 910 the teaching and learning process of Speaking English language; (2) the informants: they are the teacher of English lesson of the first grade and the students; and (3) the document. The technique of the data gathering are: (1) obseravtion; (2) indepth interview; and (3) document analysis. The observation was done to capture the teaching and learning process of speaking, indepth interview was done to test. The bvalidaty process of speaking, to get the data from document, a document analysis done are syllabus, the lesson plan the criteria of minimal achiesment and students assessment. The gathered data were analysed by using reduction, data presentation and conclusion drawing. Key word: process, during, limited, conclusion, Assessment.